2008
DOI: 10.1523/jneurosci.2084-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Crucial Role for Primary Cilia in Cortical Morphogenesis

Abstract: Primary cilia are important sites of signal transduction involved in a wide range of developmental and postnatal functions. Proteolytic processing of the transcription factor Gli3, for example, occurs in primary cilia, and defects in intraflagellar transport (IFT), which is crucial for the maintenance of primary cilia, can lead to severe developmental defects and diseases. Here we report an essential role of primary cilia in forebrain development. Uncovered by N-ethyl-N-nitrosourea-mutagenesis, cobblestone is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
156
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(171 citation statements)
references
References 78 publications
14
156
1
Order By: Relevance
“…S1B-E). In FoxG1-K3A cKO mice, cilia depletion in NEP cells leads to patterning defects and altered GLI3 processing, as previously reported (Benadiba et al, 2012;Besse et al, 2011;Higginbotham et al, 2013;Willaredt et al, 2008;Laclef et al, 2015;Fig. S1F-H).…”
Section: Ventricular Morphogenesis Defects In Ciliary Mutantssupporting
confidence: 78%
See 1 more Smart Citation
“…S1B-E). In FoxG1-K3A cKO mice, cilia depletion in NEP cells leads to patterning defects and altered GLI3 processing, as previously reported (Benadiba et al, 2012;Besse et al, 2011;Higginbotham et al, 2013;Willaredt et al, 2008;Laclef et al, 2015;Fig. S1F-H).…”
Section: Ventricular Morphogenesis Defects In Ciliary Mutantssupporting
confidence: 78%
“…Here, we used conditional knockout of ciliary genes (Ift88 and Kif3a) in Nestin-Cre mice to deplete RGCs of their primary cilium, bypassing its role in brain patterning and the polarity of neuroepithelial cells (Benadiba et al, 2012;Besse et al, 2011;Higginbotham et al, 2013;Willaredt et al, 2008;Wilson et al, 2011). Although Nestin-Cre expression starts around E10.5 in the forebrain, cilia abrogation in the VZ was complete only at E14.5, as previously shown (Liang et al, 2012; Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Importantly, a ciliary localization motif in Smo appears to control Smo translocation to the cilium (Corbit et al, 2005). Subsequent findings have demonstrated that Gli proteins and Sufu (a negative regulator of Gli) also localize to the primary cilium where, like other IFT proteins, they regulate physiological processes such as limb development and cell migration to the brain and craniofacial skeleton (Corbit et al, 2005;Han et al, 2008;Rohatgi et al, 2007;Spassky et al, 2008;Tobin et al, 2008;Willaredt et al, 2008). …”
mentioning
confidence: 99%
“…[14][15][16] Likewise, targeted deletion of Arl13b at different developmental stages in mice forebrain, although apparently not affecting the early neuroepithelium, caused the reversion of apico-basal polarity of the radial glia scaffold, with the concomitant misplacement of radially-migrating neurons. 17 Importantly, the integrity of neuroepithelial polarity has been tightly correlated with asymmetry in neurogenic cell divisions, and primary cilia may also have a role in the regulation of this process.…”
Section: Cilia and The Cell Proliferation/neurogenesis Balancementioning
confidence: 99%